Management of Lifestyle Factors in Individuals with Cirrhosis: A Pragmatic Review - Tandon, Puneeta; Berzigotti, Annalisa (Seminars in Liver Disease, 2020)
Lifestyle-related factors are major determinants/modifiers of prognosis in patients with cirrhosis. Accumulating evidence indicates that malnutrition, obesity, sedentary lifestyle, alcohol and smoking habits, and likely poor oral hygiene can increase the risk of progression of the disease, and some of them are linked to higher risk of hepatocellular carcinoma. Importantly, lifestyle-related factors can be largely corrected, and as such they represent an attractive approach to be added to etiological and pharmacological therapy in patients with cirrhosis. Nonetheless, lifestyle is often neglected in this population. In this concise review, the authors present evidence supporting lifestyle changes in patients with cirrhosis—including, but not limited to, nutrition and physical activity in malnourished and obese patients. They also discuss some elements of motivational interviews as a tool to support a better interaction between hepatologists and patients in this field.
Keywords: obesity; sarcopenia; physical activity; exercise; portal hypertension